Predictors of Unemployment After Breast Cancer Surgery: A Systematic Review and Meta-Analysis of Observational Studies - Wang, Li (J Clin Oncol, 2018)
PURPOSE: Breast cancer surgery is associated with unemployment. Identifying high-risk patients could help inform strategies to promote return to work. We systematically reviewed observational studies to explore factors associated with unemployment after breast cancer surgery. METHODS: We searched MEDLINE, EMBASE, CINAHL, and PsycINFO to identify studies that explored risk factors for unemployment after breast cancer surgery. When possible, we pooled estimates of association for all independent variables reported by more than one study. RESULTS: Twenty-six studies (46,927 patients) reported the association of 127 variables with unemployment after breast cancer surgery. Access to universal health care was associated with higher rates of unemployment (26.6% v 15.4%; test of interaction P = .05). High-quality evidence showed that unemployment after breast cancer surgery was associated with high psychological job demands (odds ratio [OR], 4.26; 95% CI, 2.27 to 7.97), childlessness (OR, 1.30; 95% CI, 1.11 to 1.53), lower education level (OR, 1.15; 95% CI, 1.05 to 1.25), lower income level (OR, 1.46; 95% CI, 1.24 to 1.73), cancer stage II, III or IV (OR, 1.43; 95% CI, 1.13 to 1.82), and mastectomy versus breast-conserving surgery (OR, 1.18; 95% CI, 1.07 to 1.30). Moderate-quality evidence suggested an association with high physical job demands (OR, 2.11; 95%CI, 1.52 to 2.93), African-American ethnicity (OR, 1.89; 95% CI, 1.21 to 2.96), and receipt of chemotherapy (OR, 1.95; 95% CI, 1.36 to 2.79). High-quality evidence demonstrated no significant association with part-time hours, blue-collar work, tumor size, positive lymph nodes, or receipt of radiotherapy or endocrine therapy; moderate-quality evidence suggested no association with age, marital status, or axillary lymph node dissection. CONCLUSION: Addressing high physical and psychological job demands may be important in reducing unemployment after breast cancer surgery.